Synthesis, Characterization and Biological Activity studies of Chromium (III) complexes of a Schiff Base Ligand - Dr Hemlata Yadav (International Journal of Scientific Research in Chemistry, 2025)
Schiff bases are an important class of organic compounds, which have a wide range of application in the field of analysis, biology and inorganic chemistry[1]. Some of these compounds are used as catalysts in polymer[2] [3] and dyes[4]. Schiff base transition Metal complexes have been used as biological models. Manganese, Cobalt, nickel, copper and zinc are important metal elements with biological activity when combined with certain proteins, participating in oxygen transport, electron transfer reactions or ion storage[5]. Schiff bases are excellent biological active compounds due to the presence of N, O or S as hetero atoms prepared by the condensation reaction of carbonye compound (aldehyde or ketone) with a primary amine. Schiff bases found to possess several biological as well as pharmacological activities[6-8].